Scheler dan Apriorisme Material Nilai dalam Perspektif Media Massa - Kardi Laksono (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Nowadays the mass media tends to inspire people to do crime. The crime which is conducted by humans actually is no other than an imitation factorwhich exists in every human. The main function of imitation is memetic which can also build a society as a product of imitation in which it will exist continuously as a social process in almost every society. Therefore, there is a need to build an ethics base, for instance Scheler’s ethics, for the mass media so that it functions to create human character based on love – ordo amoris.Keywords: Scheler’s ethics, mass media, imitation, ordo amoris.